2015
DOI: 10.1016/j.appet.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Higher weight status of only and last-born children. Maternal feeding and child eating behaviors as underlying processes among 4–8 year olds

Abstract: Birth order has been associated with childhood obesity. The objective of this cross-sectional study was to examine maternal feeding and child eating behaviors as underlying processes for increased weight status of only children and youngest siblings. Participants included 274 low-income 4-8 year old children and their mothers. The dyads completed a videotaped laboratory mealtime observation. Mothers completed the Caregiver's Feeding Styles Questionnaire and the Children's Eating Behavior Questionnaire. Child w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 50 publications
2
39
1
Order By: Relevance
“…In addition, Mosli et al, 2015 have proved that siblings have an impact on the last born child's health and nutrition, where a positive association with overweight and obesity was seen. Similar to that result, a strong positive association was also seen with the only child [48]. Future work must be directed towards involving the whole family, in relation to childhood obesity and nutrition.…”
Section: Journal Of Food and Nutrition Researchsupporting
confidence: 58%
“…In addition, Mosli et al, 2015 have proved that siblings have an impact on the last born child's health and nutrition, where a positive association with overweight and obesity was seen. Similar to that result, a strong positive association was also seen with the only child [48]. Future work must be directed towards involving the whole family, in relation to childhood obesity and nutrition.…”
Section: Journal Of Food and Nutrition Researchsupporting
confidence: 58%
“…Of the 41 studies reviewed, 17 found no association between picky eating or food neophobia and weight sta-tus 16,17,19,20,25,26,30,34,36,[40][41][42]45,[47][48][49]51 ; 2 found that picky eating or food neophobia had a positive association with overweight 13,39 ; 5 found a negative association with overweight or obesity 27,28,32,46,53 ; 6 found a positive association with underweight 11,12,21,31,35,50 ; and 11 found a decreased association with BMI or BMI z-score (but did not specify if underweight or decreased risk of overweight) 18,[22][23][24]29,33,37,38,43,44,52 (Table 2). These results are depicted in Figure 2.…”
Section: General Findingsmentioning
confidence: 99%
“…Moreover, previous literature already showed that China was undergoing a rapid nutrition transition in the past decades. The traditional Chinese diet, which is high in complex carbohydrates and fiber, had been gradually replaced by a refined food and Western food diet, which is high in fat, saturated fat, and sugar [11,[21][22][23]. As a result, the food accessibility and dietary diversity had been significantly improved in China.…”
Section: Introductionmentioning
confidence: 99%